2017
DOI: 10.1007/s12011-017-1037-8
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Determination and Cardioprotection of Terminalia pallida Fruit Ethanolic Extract in Isoproterenol Induced Myocardial Infarcted Rats by ICP-MS

Abstract: The trace elements and minerals in Terminalia pallida fruit ethanolic extract (TpFE) were determined by the instrument inductively coupled plasma-mass spectrometry (ICP-MS), and the cardioprotection of TpFE against isoproterenol (ISO)-administered rats was studied. Rats were pretreated with TpFE (100, 300, and 500 mg/kg bw) for 30 days, with concurrent administration of ISO (85 mg/kg bw) for two consecutive days. The levels of trace elements and minerals in TpFE were below the permitted limits of World Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
3
2
0
Order By: Relevance
“…Pre-treatment with COMB depressed Na + and Ca 2+ ion levels and elevated K + ion amounts in all ISO challenged rats, demonstrating the antioxidant assets of COMB in opposition to oxidation of SH groups on ATPase enzymes and preventive action of COMB against lipid peroxidation, which imply the membrane stabilization character of COMB. Our results are linear with the previous report (Althaf Hussain et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Pre-treatment with COMB depressed Na + and Ca 2+ ion levels and elevated K + ion amounts in all ISO challenged rats, demonstrating the antioxidant assets of COMB in opposition to oxidation of SH groups on ATPase enzymes and preventive action of COMB against lipid peroxidation, which imply the membrane stabilization character of COMB. Our results are linear with the previous report (Althaf Hussain et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…54 Here, our outcomes revealed that the MI rats demonstrated the depletion of K + ions and augmented the Na + and Ca +2 ion concentrations in the cardiac tissues. However, the treatment with the ponicidin remarkably decreased these ion contents and improved the K + ions in the cardiac tissues (Figure 6), which is supported by Hussain et al 55…”
Section: Discussionsupporting
confidence: 73%
“…54 Here, our outcomes revealed that the MI rats demonstrated the depletion of K + ions and augmented the Na + and Ca +2 ion concentrations in the cardiac tissues. However, the treatment with the ponicidin remarkably decreased these ion contents and improved the K + ions in the cardiac tissues (Figure 6), which is supported by Hussain et al 55 In normal cellular physiological conditions, Na + and K + ATPases maintain the Na + and K + ions transport through the membrane, upon its damage may result in ionic dissimilarity. Consequently, the measurement of the activities of membrane-bound enzymes will denote the changes in membrane physiology under pathological circumstances.…”
Section: Discussionsupporting
confidence: 68%
“…The supplementation of TpFE dose-dependently exerts notable protection on myocardium by virtue of its strong antioxidant activity. It could be used as a medicinal food for the treatment of cardiovascular ailments [163].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%